Compositional studies of seeds and fruits from two varieties of Geoffroea decorticans - Maestri, Damian (2001)
Chañar (Geoffroea decorticans) seeds and fruits constitute valuable foodstuff for humans and animals in many semiarid regions of South America. The purpose of this research was to determine the proximate composition and fatty acid pattern of seeds and fruits from two varieties of Chañar growing in Argentina. The chemical parameters evaluated varied very little among the two varieties. The most outstanding feature was the high average lipid content (about 47%) of seeds where oleic and linoleic acids accounted for 42 and 43%, respectively. The fruit composition showed similar protein and oil contents. Approximately 83% of the fatty acids were unsaturated with oleic and linoleic acids predominating. The oil yield of Chañar seeds, its physicochemical characteristics and the component fatty acids are found to be close to those reported for most commonly used edible oils.